Effect of grain morphology on degree of milling and iron loss in rice - C. Prom-u-thai (2018)
Grain morphological characteristics were thought to play a significant role in genotypic variation in Fe concentration in white rice. Comparing 17 rice cultivars representing six major grain morphological categories, the present study systematically investigated the relationship between grain morphology, the degree of milling (DOM), and the loss of Fe during the polishing process. The relative importance of key morphological parameters in this relationship was also investigated. The grain morphological characteristics of different rice cultivars significantly affected the degree of Fe loss during polishing to produce white rice. This variation in Fe loss from polishing among the six categories of rice cultivars is mainly due to their difference in DOM (r = 0.73**) and this loss in Fe was the primary factor determining the level of Fe concentration in the white rice. Among the morphological parameters investigated, grain length and length-to-width ratios played the most significant role in determining the DOM, which suggests that these two grain attributes may serve as the initial screening parameters when selecting cultivars for high Fe white rice production. Degree of Fe loss was lowest in short-bold grain shape category compared with the other grain shapes. © 2007 AACC International, Inc.